Spatial doctrines of urban development: Persistence and change in the course of time - Brigitte Adam; Guy Baudelle; Marc Dumont (Cities and metropolises in France and Germany, 2022)
In the field of urban and regional planning, France and Germany have shown several analogies since the beginning of the modern age. However, there is still a difference between more centralised governance processes (France) and a stronger position of the municipalities (Germany). But the planning strategies of France and Germany have moved closer together. A comparison covering about 100 years must differentiate between German planning strategies in East and West Germany for a considerable period. Urban planning has been influenced by similar models like the Athens Charter or the Leipzig Charter. The latter, a European document, was renewed in 2020. Furthermore, in both countries, similar paths can be identified: the pursuit of a strong technical focus, the tendency towards sustainable development, more flexibility, the growing importance of integrated policies and the challenges of urban sprawl. Main doctrines like integration, participation and future orientation have accompanied urban and regional planning in Germany as well as in France.
urn:nbn:de:0156-1119033; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Integration; sustainable development; competitiveness; participation; open spaces